Organisation, management and optimisation of ready mixed concrete delivery for commercial batching plants of Western India. (5th August 2020) - Sarkar, Debasis; Gohel, Jishnu; Dabasia, Keval
This paper is an attempt to organise, manage and develop a delivery schedule model with real time data for a commercial ready mixed concrete (RMC) plant in Ahmedabad city of Gujarat in Western India. Without a proper delivery schedule, either a truck-mixer would need to wait for the concrete to be placed at site or the construction site would need to wait for the truck-mixer to arrive on time. It has been observed after 101 iterations in MATLAB software that the dispatch scheduling sequence 1, 2, 2, 1, 1, 3, 2, 3, 2, 3, 3, 3 has the least total waiting time of 155.4 minutes. After validating the same model with real time data, it has been observed that for the above dispatching sequence, the total waiting time is 153 minutes with one obstruction resulting in a delay of 48 minutes for the casting of concrete at site. Furthermore, based on the computations, it is recommended that the plant authorities need to increase the number of RMC truck-mixers from five to seven for uninterrupted and smooth delivery of RMC from plant to site.